Milia-like idiopathic calcinosis cutis of the medial canthus - Faten Limaiem; Sirine Bouslema; Inès Haddad; Fadoua Abdelmoula; Saâdia Bouraoui; Ahlem Lahmar; Sabeh Mzabi (Our Dermatology Online, 2013)
Calcinosis cutis is a term used to describe a group of disorders in which calcium deposits form in the skin and may be classified as dystrophic, metastatic, idiopathic or iatrogenic calcification, and calciphylaxis. Idiopathic calcinosis cutis occurs without any underlying tissue damage or metabolic disorder. In this paper, the authors report a new case of idiopathic calcinosis involving the medial canthus of the left eye that was mistaken for milia. An 18-year-old previously healthy male patient, presented with an asymptomatic whitish solitary tumour of the medial canthus of the left eye. The patient had no systemic or trauma history, and the serum levels of calcium and phosphorous were normal. An excisional biopsy was performed and histopathologic examination revealed subepidermal calcinosis. Calcinosis cutis is a rare condition that should be included in the differential diagnosis of a benign-appearing lesion of the face. While it can occur in patients with a history of inflammation, trauma, or hypercalcemia, its etiology can also be idiopathic.